1995
DOI: 10.1139/g95-081
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity in wild and cultivated sorghum

Abstract: Cultivated sorghum (Sorghum bicolor ssp. bicolor) is classified into five main races on the basis of spikelet morphology. Isozyme analyses provided new insight into the genetic diversity of sorghum and revealed marked geographic grouping, while nuclear restriction fragment length polymorphisms showed racial differentiation and intraguinea race differentiation. Wild sorghum is diploid or tetraploid and African sorghum (S. bicolor ssp. arundinaceum) is classified into four races, that are considered to be progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
5
32
0
1
Order By: Relevance
“…Levels and patterns of diversity within and between cultivated and wild sorghum gene pools have been reported before (e.g Morden et al 1990;Cui et al 1995;Deu et al 1995;Casa et al 2005). These previous studies have shown that (i) there is low to moderate genetic differentiation among cultivated and wild sorghum gene pools, (ii) portions of the wild gene pool most genetically similar to cultivars originated in central-north-east Africa and (iii) genetic diversity is greater in wild-weedy than in cultivated sorghums.…”
Section: Introductionmentioning
confidence: 66%
“…Levels and patterns of diversity within and between cultivated and wild sorghum gene pools have been reported before (e.g Morden et al 1990;Cui et al 1995;Deu et al 1995;Casa et al 2005). These previous studies have shown that (i) there is low to moderate genetic differentiation among cultivated and wild sorghum gene pools, (ii) portions of the wild gene pool most genetically similar to cultivars originated in central-north-east Africa and (iii) genetic diversity is greater in wild-weedy than in cultivated sorghums.…”
Section: Introductionmentioning
confidence: 66%
“…PCR and DNA sequencing: Genomic DNA was extracted from fresh leaves harvested from a single 3-week seedling per accession following a cetyltrimethylammonium bromide (CTAB) protocol previously described (Deu et al 1995). SP6 (59-GATTTAGGTGACACTATAG-39) and T7 (59-TAATACGA CTCACTATAGGGC-39) tails were added to the 59 ends of primers to facilitate direct sequencing of the PCR products.…”
Section: Plant Materialmentioning
confidence: 99%
“…bicolor), namely bicolor, caudatum, durra, guinea, and kafir, as well as 10 intermediate types. This species has been studied with various types of molecular markers (Ollitrault et al 1989;Aldrich et al 1992;Deu et al 1994Deu et al , 1995Cui et al 1995;De Oliveira et al 1996;Menkir et al 1997;Djè et al 2000;Grenier et al 2000;Casa et al 2005) and has recently undergone detailed sequence diversity analysis using small representative panels of diverse accessions (Hamblin et al 2004(Hamblin et al , 2006, which enabled investigation of linkage disequilibrium (LD) and patterns of selection among several hundred loci. This resulted in a fine understanding of ecogeographic patterns of variation in sorghum, in particular with reference to its geographic spreading out of the area of origin in the northeastern part of sub-Saharan Africa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Levels and patterns of diversity within and between cultivated and wild sorghum gene pools have been reported (Cui et al, 1995;Deu et al, 1995;Casa et al, 2005). In Kenya, studies were done to establish the extent and direction of introgression between cultivated and wild sorghum relatives (Mutegi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%